Preface to the special issue of the international symposium on solid mechanics (Mecsol 2017) - Vaz M.* (2018)
© 2018, Brazilian Association of Computational Mechanics. All rights reserved.The International Symposium on Solid Mechanics (MecSol) is a biennial conference which aims to provide a forum to discuss relevant issues associated with solid mechanics. The MecSol 2017 edition was held in the city of Joinville, Brazil, on 26-28 April 2017. Plenary lectures were delivered by researchers from five different countries. The main topics discussed in the conference are as follows: composite materials, optimization, constitutive modelling, fatigue, impact, nonlinear analyses, structural reliability, X-FEM, G-FEM, and BEM numerical methods. The participants were invited to submit full papers, which, after peer review, compound this special issue of the Latin American Journal of Solids and Structures. This article highlights the main topics addressed in the conference.